Թուրքմենչայի պայմանագրի կնքման գործում Ա. Ա. Գրիբոյեդովի մասնակցության հարցը խորհրդային պատմագրության գնահատմամբ - Վահրամ Սիմոնյան (ՀՀ ԳԱԱ հրատ.)
Армянская церковь и представители национальной интеллигенции ясно осознавали историческое значение момента после окончания русско-персидской войны и при составлении договора хотели использовать этот шанс для освобождения части армян от мусульманского ига. Именно они попытались уговорить русских деятелей ввести в договор статьи, касающиеся армян (ст. III,IV, т. е. "присоединение Восточной Армении к России", ст. XV—"переселение армян"). Both the Armenian intellectuals and the Armenian church were clearly conscious of the istorical significance of the moment after the end of the Russian-Persian war and in signing the agreement wanted to take the chance for liberation of a part of the Armenian people from the Moslem yoke. They themselves did their best to persuade the Russian figures to include the indicated articles in the agreement concerning the Armenians (art. Ill, IV, i.e. «Annexation of Eastern Armenia with Russia», art. XV «Migration of Armenians»).
Keywords: History; Literature; Language and Literature; Diplomacy; D History; J Political Science